Warkah-warkah Sultan Buton Muhyiuddin Abdul Gafur kepada kompeni Belanda, Koleksi Universiteitsbibliotheek Leiden - Suryadi (Universiti Kebangsaan Malaysia, 2007)
A prominent collection of Butonese manuscript are those known as the Butonese royal letters. They were sent to local authorities in the Nusantara region, particularly those situated in the eastern part of the archipelago, as well as to the Dutch. A sovereign maritime kingdom situated in the eastern part of Indonesia, the Sultanate of Buton was established in the 14th century and disappeared as a polity in 1960 after it’s integration into the Republic of Indonesia. This paper looks at five royal letters that Sultan Muhyiuddin Abdul Gafur, the 26th Butonese Sultan, who reigned from 1791 to1799, sent to the Dutch Governor-General of East Indies in Batavia. Written between 1788 and 1798, they are now preserved in Leiden University Library in the Netherlands. Herewith is presented a transliteration of these five letters, which touch on their intrinsic aspects. Through it, some historical events that occurred in the Sultanate of Buton during Sultan Muhyiuddin Abdul Gafur’s reign are reconstructed